On ambiguity of objective image quality assessment. Issue 1 (1st January 2016) - Cheon, M.; Lee, J.‐S.
Abstract : The issue of ambiguity of objective image quality assessment is addressed. The necessity of considering perceptual ambiguity of two objective quality scores is justified first. Then, an approach to obtain an ambiguity interval defining the quality score range is developed within which quality difference is not perceptually distinguishable. Experimental results demonstrate the validity of the developed approach and examine various aspects of the ambiguity of objective quality assessment in viewpoints of the type of image distortion, objective quality metric, image content etc.